A cognitive assessment tool For IAQ - cognitive health study - Lim, Kok Jiang (2018)
Poor indoor quality can cause a decrease in productivity and working performance, this is one of the common problems in cities where people spend 90% of their time indoor. However, a scheme to evaluate the working performance in different environment under different indoor air quality parameter is still undeveloped. Cognitive assessment can be a good form of evaluating the occupants working performance effectively. The assessment can not only identify but quantify how difference assessment may affect different cognitive abilities. Methods that was used to develop the cognitive assessment tool is based on the brain functionality. Brain can be classified into cerebellum and different lobes; frontal, parietal, occipital, temporal. Each lobe and cerebellum give rise to different domains in the brain. Six cognitive tests were developed and used in this experiment; Mental Arithmetic Test, Quadrato Motor Training, Stroop Effect Test, Remote Associates Test, Raven’s Progressive Matrices and Working Memory Test. Experiment was conducted in indoor air condition and non-air condition environment. From the results, there was significant difference in the cognitive test conducted in both air-condition and non-air condition environment respectively, where p-value is less than 0.05. This is an indication that the results from the cognitive test is significant and robust in producing test results. On the other hand, when comparing the test results (air condition vs non-air condition), p-value obtained was more than 0.05. This value gives an indication that there is no significant difference when comparing the cognitive result for air condition vs non-air condition. In conclusion, cognitive assessment tool has a potential to analyze occupant in different environment.